Exercise training-induced speeding of VO2 kinetics is not intensity domain-specific or correlated with indices of exercise performance - Erin Calaine Inglis (7042334) (2024)
Purpose This study examined the effect of 3 and 6 weeks of intensity domain-based exercise training on VO2 kinetics changes and their relationship with indices of performance. Methods Eighty-four young healthy participants (42 M, 42 F) were randomly assigned to six groups (14 participants each, age and sex-matched) consisting of: continuous cycling in the (1) moderate (MOD)-, (2) lower heavy (HVY1)-, and (3) upper heavy-intensity (HVY2)- domain; interval cycling in the (4) severe-intensity domain (i.e., high-intensity interval training (HIIT), or (5) extreme-intensity domain (i.e., sprint-interval training (SIT)); or (6) control (CON). Training participants completed two three-week phases of three supervised sessions per week, with physiological evaluations performed at PRE, MID and POST intervention. All training protocols, except SIT, were work-matched. Results There was a significant time effect for the time constant (τ VO2 ) between PRE (31.6 ± 10.4 s) and MID (22.6 ± 6.9 s) (p < 0.05) and PRE and POST (21.8 ± 6.3 s) (p < 0.05), but no difference between MID and POST (p > 0.05) and no group or interaction effects (p > 0.05). There were no PRE to POST differences for CON (p < 0.05) in any variables. Despite significant increases in maximal VO2 (VO2max ), estimated lactate threshold (θLT), maximal metabolic steady state (MMSS), and peak power output (PPO) for the intervention groups (p < 0.05), there were no significant correlations from PRE to MID or MID to POST between ΔτVO2 and Δ V O2max (r=– 0.221, r = 0.119), ΔPPO (r= – 0.112, r= – 0.017), ΔθLT (r= 0.083, r = 0.142) and ΔMMSS (r= – 0.213, r = 0.049)(p > 0.05). Conclusion This study demonstrated that (i) the rapid speeding of VO2 kinetics was not intensity-dependent; and (ii) changes in indices of performance were not significantly correlated with ΔτVO2. Other Information Published in: European Journal of Applied Physiology License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s00421-024-05674-1